The Morphometry of Impact Craters on Bennu. Issue 24 (13th December 2020) - Daly, R. T.; Bierhaus, E. B.; Barnouin, O. S.; Daly, M. G.; Seabrook, J. A.; Roberts, J. H.; Ernst, C. M.; Perry, M. E.; Nair, H.; Espiritu, R. C.; Palmer, E. E.; Gaskell, R. W.; et al.
Abstract: Bennu is an 500‐m‐diameter rubble‐pile asteroid that is the target of detailed study by the Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS‐REx) mission. Here we use data from the OSIRIS‐REx Laser Altimeter to assess depth‐to‐diameter ratios ( d/D) of 108 impact craters larger than 10 m in diameter. The d/D of craters on Bennu ranges from 0.02 to 0.19. The mean is 0.10 ± 0.03. The smallest craters show the broadest range in d/D, consistent with d/D measurements on other asteroids. A few craters have central mounds, which is interpreted as evidence that a more competent substrate lies a few meters beneath them. The range of d/D narrows as crater size increases, with craters larger than 80 m tending toward smaller d/D . At large scales, increases in target strength with depth, combined with target curvature, may affect crater morphometry. Plain Language Summary: Between 2018 and 2020, National Aeronautics and Space Administration (NASA)'s Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS‐REx) spacecraft orbited a small asteroid called Bennu in preparation to collect a sample for return to Earth. Bennu is a "rubble‐pile" asteroid, meaning an aggregate of rock fragments that have coalesced together in space. OSIRIS‐REx observations showed that Bennu has many craters on its surface, which formed when other, smaller objects collided with it in the past. Crater depths and widths (diameters), in addition to relating to the size and speed of the impacting object, also reflect the physical characteristics of the impacted surface. Accordingly, we measured the depths and diameters of many of Bennu's craters to better understand the surface and interior properties of this rubble‐pile asteroid and how it compares to other asteroids. The smaller craters on Bennu have a variety of depths, even among similarly sized craters. The largest are so wide that they appear to be affected by the curvature of Bennu's surface and by the presence of stronger material at depth. We observe mounds inside some of the smaller craters, supporting the idea that a more competent substrate underlies the surface material. Key Points: The depth‐to‐diameter ratio ( d/D ) of asteroid Bennu's craters >10 m in diameter ranges from 0.02 to 0.19 with a mean of 0.10 ± 0.03 Small craters show the greatest diversity in d/D, whereas larger craters (>80 m) span a narrower range in d/D and tend to be shallower For craters >80 m, increases in target strength with depth, combined with target curvature, likely contribute to smaller d/D